2012
DOI: 10.1111/j.1365-4632.2012.05522.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF‐α polymorphisms with adult dermatomyositis and systemic lupus erythematosus in Bulgarian patients

Abstract: The TNF-α polymorphisms are associated with increased relative risk mainly for SLE, particularly in women, while their role for DM is less evident and needs further analysis in an enlarged sample cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…There are several polymorphisms in the promoter region of the TNF gene (−308A/G, −238G/A, +489G/A, −1031T/C, −863C/A, −857C/T) [43]. Some studies had investigated the relationship between TNF-α-238A/G, +489 A/G, −1031T/C, −863C/A, −857C/T polymorphisms and the susceptibility to DM [11], [14]–[15], [17], we also summarized the characteristics of studies and populations on the association between other TNF polymorphisms and DM risk (The details of the characteristics were provided in Table S1, S2A, S2B, S2C, S2D in File S1). And we did meta-analysis on the association between the TNF-α-238A/G, +489 A/G, −1031T/C, −863C/A, −857C/T polymorphisms and the susceptibility to DM (The details of the results were provided in Table S3 in File S1).…”
Section: Discussionmentioning
confidence: 99%
“…There are several polymorphisms in the promoter region of the TNF gene (−308A/G, −238G/A, +489G/A, −1031T/C, −863C/A, −857C/T) [43]. Some studies had investigated the relationship between TNF-α-238A/G, +489 A/G, −1031T/C, −863C/A, −857C/T polymorphisms and the susceptibility to DM [11], [14]–[15], [17], we also summarized the characteristics of studies and populations on the association between other TNF polymorphisms and DM risk (The details of the characteristics were provided in Table S1, S2A, S2B, S2C, S2D in File S1). And we did meta-analysis on the association between the TNF-α-238A/G, +489 A/G, −1031T/C, −863C/A, −857C/T polymorphisms and the susceptibility to DM (The details of the results were provided in Table S3 in File S1).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to analyze the TNF-α serum concentrations in patients with DM and SLE and search for correlations on terms of the TNF-α polymorphisms we have studied earlier. 4,5…”
Section: Original Article Medicinementioning
confidence: 99%
“…In previous studies, we have found that the TNF-α -1031C/-863C/-857C/-308G/+489G haplotypes are associated with both DM and SLE, especially in women. 4,5 Although there are plenty of studies, the data concerning the role of TNF-α polymorphisms in its secretion vary a lot. In an in vitro study, the TNF-α level and the transcriptional promoter activity produced by concanavalin Aactivated peripheral blood mononuclear cells were higher for the -857T or -1031C alleles than for the -857C or -1031T alleles, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine secretion was found to be under genetic control [2]. In our previous study, we have found association between TNF- α polymorphisms and the etiology of DM and SLE in Bulgarian patients [3]. …”
Section: Introductionmentioning
confidence: 99%